2018
DOI: 10.1155/2018/3861079
|View full text |Cite
|
Sign up to set email alerts
|

CD4hiCD8lowDouble-Positive T Cells Are Associated with Graft Rejection in a Nonhuman Primate Model of Islet Transplantation

Abstract: Peripheral CD4/CD8 double-positive (DP) T cells are associated with autoimmune disorders, cancer, and viral infection. However, the relationship between organ transplantation and DP T cells is unclear. Here, we examined the functional characteristics of peripheral DP T cells and analyzed their significance with respect to islet graft rejection in a nonhuman primate model of islet transplantation. DP T cells were functionally equivalent to conventional CD4 and CD8 T cells in terms of helper and cytotoxic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 51 publications
2
19
0
2
Order By: Relevance
“…Additionally, CD4 CTL-like cells, which exhibit cytotoxic properties, were also identi ed in the NKG2D + cells of the CD4 hi CD8 lo fraction. Given these cytotoxic characteristics, these data support previous ndings that peripheral DP cell populations are increased under chronic in ammatory conditions, such as transplantation 4 and viral infection 9 , as well as in cancer patients 40 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, CD4 CTL-like cells, which exhibit cytotoxic properties, were also identi ed in the NKG2D + cells of the CD4 hi CD8 lo fraction. Given these cytotoxic characteristics, these data support previous ndings that peripheral DP cell populations are increased under chronic in ammatory conditions, such as transplantation 4 and viral infection 9 , as well as in cancer patients 40 .…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the phenotypic properties and functional roles of circulating DP T lymphocytes have not been characterized completely. For instance, in a previous study 4 , we found that some DP T cells express signi cant levels of promyelocytic leukemia zinc nger (PLZF) 15 and eomesodermin (Eomes) 16 , both markers of innate lymphocytes, when compared with CD4 SP and CD8 SP T cells. In this respect, DP T cells may be another type of innate-like T cell and so may be considered to be cells with similar characteristics.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Данное наблюдение подтверждает недавние результаты исследования (Y.J. Choi et al, 2018), указывающие на роль периферических ДП Т-клеток в модели трансплантации островков поджелудочной железы. Было обнаружено увеличение уровня CD3 + CD4 + CD8 + Т-лимфоцитов в экспериментальной группе животных, в которой наблюдалось отторжение трансплантата.…”
Section: материал и методыunclassified
“…Что касается роли данной субпопуляции в трансплантологии, некоторыми авторами показано, что увеличение количества ДП Т-клеток в модели трансплантации островков поджелудочной железы было ассоциировано с отторжением трансплантата. Учитывая полученные данные, авторы предположили, что периферические ДП Т-клетки, обладающие как хелперной, так и цитотоксической активностью in vitro, могут выступать в качестве нового биомаркера для диагностики отторжения [7].…”
Section: Introductionunclassified